Chapter Introduction A Balkan Laboratory of Citizenship - Štiks, Igor (Bloomsbury Academic, 2015)
The introductory chapter explains why Yugoslavia and the post-Yugoslav region, due to frequent constitutional changes, provides such an interesting and insightful example for studying modern politics and it shows why citizenship offers necessary lenses to understand political and social processes. It explains what do we mean by citizenship, in theory and practice, and why we introduce a heuristic concept of citizenship regime that encompasses legal and administrative side of inclusion and exclusion, social and political dynamic of membership and the influence of ideologies and everyday experiences of citizenship. The introduction shows the â citizenship gapâ in the literature covering the former Yugoslavia, the ideological conflicts over the concept and its practices and their inexplicable marginalization in the scholarship focused on the construction and, mostly, destruction of Yugoslavia. It also defines modern citizenship as a tool for various political and social purposes in this region over the last century. A study of transformations of citizenship represents thus an alternative political history of Yugoslavia and the post-Yugoslav states.